GM-CSF production from human airway smooth muscle cells is potentiated by human serum - Maria B. Sukkar; J. Margaret Hughes; Peter R. A. Johnson; Carol L. Armour (Mediators of Inflammation)
Recent evidence suggests that airway smooth muscle cells (ASMC) actively participate in the airway inflammatory process in asthma. Interleukin–1β (IL–1β) and tumour necrosis factor–α (TNF–α) induce ASMC to release inflammatory mediators in vitro. ASMC mediator release in vivo, however, may be influenced by features of the allergic asthmatic phenotype. We determined whether; (1) allergic asthmatic serum (AAS) modulates ASMC mediator release in response to IL–1β and TNF–α, and (2) IL–1β/TNF–α prime ASMC to release mediators in response to AAS. IL–5 and GMCSF were quantified by ELISA in culture supernatants of; (1) ASMC pre-incubated with either AAS, non-allergic non-asthmatic serum (NAS) or MonomedTM (a serum substitute) and subsequently stimulated with IL–1β and TNF–α and (2) ASMC stimulated with IL–1β/TNF–α and subsequently exposed to either AAS, NAS or MonomedTM. IL-1g and TNF–α induced GM-CSF release in ASMC pre-incubated with AAS was not greater than that in ASMC pre-incubated with NAS or MonomedTM. IL–1β and TNF–α, however, primed ASMC to release GM-CSF in response to human serum. GM-CSF production following IL–1β/TNF–α and serum exposure (AAS or NAS) was significantly greater than that following IL–1β /TNF–α and MonomedTM exposure or IL–1β/TNF–α exposure only. Whilst the potentiating effects of human serum were not specific to allergic asthma, these findings suggest that the secretory capacity of ASMC may be up-regulated during exacerbations of asthma, where there is evidence of vascular leakage.